Tele-proximity: Tele-community of Inquiry Model. Facial Cues for Social, Cognitive, and Teacher Presence in Distance Education - Themeli, Chryssa; Bougia, Anna (International Review of Research in Open and Distributed Learning, 2016)
Distance education is expanding in all continents, and the use of video has dominated internet. Synchronous Video Communication (SVC) has not been an option thoroughly investigated and practitioners, who use and design synchronous learning scenarios, are in urgent need of guidance. Distant learners face many barriers, and as a result, they drop out more frequently than on-campus students. Educators seem to be equally affected by the “transactional distance” and the new digital literacies needed for facilitating online learning. This study explores the educators’ perspective on how SVC could offer alternative educational forms and possibilities for distance learning. Findings had indicated that the use of visual communication and human to human contact (prosopogonosia: seeing faces) could have a strong impact on learning and teaching, therefore, a theory called Tele-proximity was formulated. Tele-proximity is defined as online embodiment that explains how instructors and students are connected in synchronous networked environment via tele-operations. SVC creates a sense of place or a stage where online identities perform and highlights recent research on audio-visual signals in communication and team work (Pentland, 2012, 2008). The theory can be seen as an extension of the Community of Inquiry Model (Garrison, Anderson & Archer, 2000) and a theoretical framework according to which learning objectives could be designed. Transactional distance could be minimized and may be implemented to facilitate more synchronous, visual, and humane options in distance education.